Implementasi penggunaan aplikasi keuangan dalam meningkatkan efektivitas pengelolaan keuangan - Tutik Indraswati; Arie Rachma (Nur Science Institute, 2026)
This study aims to analyze the implementation of the “SekolahKu” financial application in improving the effectiveness of financial administration at SMP Muhammadiyah Plus Klaten Utara. The study employs a qualitative case study approach. Data were collected through semi-structured interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that implementing the “SekolahKu” financial application enhances the effectiveness of financial administration through four key aspects: improved data security, accelerated financial reporting, increased record-keeping accuracy, and the provision of more relevant, easily accessible information. System automation and integration also support more effective, transparent, and accountable school financial management. Thus, the implementation of the financial application has improved the quality of school financial management.